The AVAIL NE study - Awidi, Abdalla (2019)
Background: Venous Thromboembolism (VTE) is a global cause of morbidity and mortality with annual incidence rates between 0.75 and 2.69 per 1000 individuals in the population. Despite the large variety of VTE prophylactic solutions and the availability of several guidelines for their use, appropriate prophylaxis practices are not ideal in many healthcare facilities around the world. Objectives: The present study aimed to evaluate the extent of administration of the recommended prophylactic treatment to hospitalized patients at risk of VTE according to local protocols and/or national/international guidelines. Methods: This observational, cross-sectional study was conducted on 1256 medical and surgical patients from 26 sites across the Near East region. The patients' records were screened for the fulfillment of inclusion/exclusion criteria during a single visit. The proportion of medical and surgical patients who were at risk of VTE and the thromboprophylactic measures employed by physicians for these patients were assessed. Results: The results demonstrated that 559 patients (52.2%) did not require thromboprophylaxis. Yet, 17.8% were inappropriately administered a prophylactic treatment. Out of the 512 patients at risk of VTE, 443 were eligible for drug prophylaxis. However, 50% received the recommended treatment. Furthermore, significant variations were observed among centers in different countries regarding prophylactic measures in critically ill, cancer, chronically immobilized, and non-orthopedic surgery patients. Conclusion: Despite the universal acknowledgment of the seriousness of VTE, the employment of thromboprophylaxis remains suboptimal in the Near East region. A considerable number of hospitalized patients are not receiving any VTE prophylaxis or are given inappropriate treatments. Further studies are required to assess and compare compliance rates prior to and following the implementation of such quality improvement projects.